Ghana : Staff Report for the 2003 Article IV Consultation, and Requests for a Three-Year Arrangement Under the Poverty Reduction and Growth Facility and for Additional Interim Assistance Under the Enhanced Initiative for Heavily Indebted Poor Countries. (IMF Staff Country Reports; Country Report ;, 2003)
This paper assesses Ghana's 2003 Article IV Consultation, and Requests for a Three-Year Arrangement Under the Poverty Reduction and Growth Facility (PRGF) and for Additional Interim Assistance Under the Enhanced Initiative for Heavily Indebted Poor Countries (HIPC). Program implementation in 2002 was mixed. Further gains were made on inflation, and the reserve accumulation target was met. In view of the strength of the authorities' program, including the prior actions to be taken, the IMF staff supports the request for a three-year PRGF arrangement in the amount of SDR 184.5 million, and for additional interim HIPC relief.